Penyuluhan Nilai-nilai Perjuangan Melalui Tugu Gerilyawan Pejuang 1945 Pada Masyarakat Koto Tangah Kota Padang - kaksim kaksim; meldawati meldawati; zulfa zulfa; refni yulia (Universitas PGRI Sumatera Barat, 2023)
Koto Tangah Subdistrict is the district with the largest area among other districts in the city of Padang. As the largest subdistrict, it has various potentials in terms of territory, tourism, markets, education, healthcare facilities, and others. In addition to these potentials, based on its history, Koto Tangah Subdistrict has been considered important long before it became the city center. This can be seen from the emergence of prominent figures, especially during the physical revolution era. During this period, various movements occurred to defend Indonesia's independence, and there were numerous instances of resistance from the Koto Tangah fighters in the form of guerrilla warfare. The guerrilla resistance is evident through the existence of the